Sustainable Shipping Practices: A Review of Environmental Initiatives in the Maritime Industry - Yusup, Muhammad Firdaus Bin (Maritime Park: Journal of Maritime Technology and Society, 2023)
Maritime transportation, a cornerstone of global trade, faces escalating concerns over its environmental impact. This review critically examines sustainable shipping practices, presenting a thorough analysis of environmental initiatives within the maritime industry. The primary objective is to offer a comprehensive overview of measures adopted to mitigate the ecological footprint associated with shipping operations. Commencing with an exploration of the environmental challenges linked to traditional shipping practices, the review underscores issues such as air and water pollution, greenhouse gas emissions, and the ecological ramifications of ballast water discharge. The urgency to adopt sustainable practices is emphasized in light of tightening regulations and the imperative to address these environmental challenges.